Individual and society : sociological social psychology - Crawford, Lizabeth A.; Novak, Katherine B. (Abingdon, Oxon : Routledge, 2014)
'Unlike the few other texts for undergraduate sociological social psychology courses that present 3 distinct traditions (or'faces') ...Symbolic Interactionist (SI), Social Structure and Personality (SSP), and Group Processes and Structure (GPS) by topic alone, this text initially discusses these'faces' by research tradition, and emphasizes the different theoretical frameworks within which social psychological analyses are conducted. With this approach, the authors make clear the link between'face' of sociological social psychology, theory, and methodology. And students gain an appreciably better understanding of the field of sociological social psychology; how and why social psychologists trained in sociology ask particular kinds of questions; the types of research they are involved in; and how their findings have been, or can be, applied to contemporary societal patterns and problems. Great writing makes this approach successful and interesting for students, resulting in a richer, more powerful course experience. A website offers instructors high quality support material, written by the authors, which you will appreciate and value'--
Includes bibliographical references (pages 473-5140 and index.
Keywords: Social psychology; Social psychology -- Research